Modeling and Optimization of Carbon Dioxide Removal in Packed Bed Column Reactor - Thirugnanasambandham, K. (Asian Journal of Engineering and Applied Technology, 2019)
Global warming due to greenhouse gases has become a serious global issue. Extensive efforts are being made to fighting this phenomenon through carbon capture as carbon dioxide (CO2) is its major contributor. This study focused on CO2 capture in packed bed column reactor using Poly-(D) glucosamine under the various process parameters such as temperature, feed flow rate and mass of the adsorbent. Statistical design of experiments was carried out in order to analysis the effect process parameters on the capacity of CO2 capture in packed bed column. The obtained results show that feed flow rate has the significant affect compared to others. The maximum of 956 mg of CO2 is captured under the following operating conditions; temperature of 40oC, feed flow rate of 30 ml/min and 0.25 g of the Poly-(D) glucosamine. The ability of Poly-(D) glucosamine to capture the CO2 in packed bed column is confirmed.